Rooting out faulty adsorption models. Comment on “Magnetic Prussian blue nanoshells are controllable (sic) anchored on the surface of molybdenum disulfide nanosheets for efficient separation of radioactive cesium from water” - Chu, Khim Hoong; Hashim, Mohd Ali; Hayder, Gasim; Bollinger, Jean-Claude (The Science of the total environment, 2024)
This correspondence critically examines and rectifies modeling deficiencies identified in a recent article published in this journal. Our analysis covers a range of models and issues, including the Temkin isotherm, the Flory–Huggins isotherm, the pseudo-first-order kinetic model, the pseudo-second-order kinetic model, the intraparticle diffusion model, the Elovich kinetic model, and the computation of thermodynamic parameters. The elucidation and correction of these modeling issues contribute to a more accurate and reliable understanding of the studied phenomena, thereby enhancing the scientific rigor of the subject paper.